A systematic review of the efficacy and general safety of antibodies to NGF in the treatment of OA of the hip or knee. (January 2015) - Schnitzer, T.J.; Marks, J.A.
Summary: To evaluate the efficacy and safety of anti-NGF antibody treatment in hip and knee osteoarthritis (OA), a systematic review and meta-analysis was undertaken utilizing the criteria described by the Cochrane collaboration. Both published and unpublished trials were identified for tanezumab, fulranumab and fasinumab in hip and knee OA; sponsors were contacted to provide and confirm data. Study quality was assessed by Jadad criteria; efficacy and safety data were extracted independently by two individuals and meta-analyses were performed using Revman 5.2. 13 randomized, controlled trials were identified: 10 of tanezumab, two of fulranumab and one with fasinumab. All agents demonstrated superiority in efficacy compared to placebo. The highest doses in the phase II studies of tanezumab had a standardized effect size for WOMAC pain of 0.73 (CI, 0.51, 0.95). Subsequent phase III studies of tanezumab and phase II studies of fulranumab and fasinumab reported standardized effect sizes for WOMAC pain of −0.15–0.5, with no clear distinction among dose levels. Tanezumab compared to NSAIDs and opioids showed greater efficacy with a standardized effect size for WOMAC pain of 0.23 (CI 0.17–0.29). WOMAC function and PGA results were similar to WOMAC pain. Safety, determined by odds ratios of withdrawals from studies due to adverse events (AEs), was better at the lower doses than higher doses and similar among all agents. These results demonstrate that antibodies to NGF provide efficacy in OA and that general safety at the lower doses appears similar to placebo. Additional data on both efficacy and safety of these antibodies are needed to define the optimal dose to maximize benefit to risk.